Evoked potential changes in patients with Parkinson's disease. Issue 5 (7th April 2017) - Liu, Chunyan; Zhang, Yaping; Tang, Weiguo; Wang, Binda; Wang, Bona; He, Songbin
Abstract: Objective: Patients with Parkinson's disease (PD) may have sensory dysfunction, and it can be more easily demonstrated through electrophysiologic testing. We aimed to explore whether the impairment of brainstem visual and auditory passageway exists in PD patients using visual evoked potential (VEP) and brainstem auditory evoked potential (BAEP) examinations. Methods: Forty‐two PD cases and thirty controls participated in the study. All subjects underwent the VEP and BAEP examinations. The N75, P100, N145 latencies and P100 amplitude of VEP, the latencies of waves I, III, V and the interpeak latencies (IPL) of waves I–III, III–V, I–V were measured. Results: The N75, P100, N145 latencies of VEP, but not the amplitude of P100, were significantly longer in patients with PD than the control group ( p < .05). The latencies of wave III and wave V, the IPL of III–V and I–V were all significantly increased compared with control subjects while no significant difference was noted in waves I and I–III IPL. Conclusion: Our results found that brainstem visual and auditory passageway may be impaired in PD patients. Significance: VEP and BAEP can be served as sensitive measurements in helping prognosis and assessment the severity of the disease. Abstract : The N75, P100, N145 latencies of VEP, but not the amplitude of P100, were significantly longer in patients with PD than the control group . The latencies of wave III and wave V, III‐V interpeak latency (IPL), and I‐V IPL were all significantly increased in PD patients compared with control subjects while no significant difference was noted in wave I and I‐III IPL.